Effects of Metal Micro and Nano-Particles on hASCs: An In Vitro Model - Palombella, Silvia (Nanomaterials (Basel), 2017)
As the knowledge about the interferences of nanomaterials on human staminal cells are scarce and contradictory, we undertook a comparative multidisciplinary study based on the size effect of zero-valent iron, cobalt, and nickel microparticles (MPs) and nanoparticles (NPs) using human adipose stem cells (hASCs) as a model, and evaluating cytotoxicity, morphology, cellular uptake, and gene expression. Our results suggested that the medium did not influence the cell sensitivity but, surprisingly, the iron microparticles (FeMPs) resulted in being toxic. These data were supported by modifications in mRNA expression of some genes implicated in the inflammatory response. Microscopic analysis confirmed that NPs, mainly internalized by endocytosis, persist in the vesicles without any apparent cell damage. Conversely, MPs are not internalized, and the effects on hASCs have to be ascribed to the release of ions in the culture medium, or to the reduced oxygen and nutrient exchange efficiency due to the presence of MP agglomerating around the cells. Notwithstanding the results depicting a heterogeneous scene that does not allow drawing a general conclusion, this work reiterates the importance of comparative investigations on MPs, NPs, and corresponding ions, and the need to continue the thorough verification of NP and MP innocuousness to ensure unaffected stem cell physiology and differentiation.